Norges Bank's Output Gap Estimates - Marianne Sturød; Kare Hagelund (Norges Bank, 2012)
The output gap quantifies aggregate capacity utilisation in the economy. Norges Bank's output gap assessment starts with a trend calculation (HP filter) of mainland GDP. Such trend estimates are inherently subject to uncertainty, particularly towards the end of the sample period. We therefore adjust the estimates based on other key information about capacity utilisation in the economy. The most important sources of adjustments are reviewed in this paper. In our assessments, particular emphasis is given to developments in the labour market. Unemployment is a good measure of welfare and provides a good gauge of the level of economic activity. As labour market figures are published regularly and seldom revised, they are therefore very useful in real-time assessment of capacity utilisation in the economy. In our assessment of capacity utilisation in enterprises, particular emphasis is given to the reports from Norges Bank's regional network.
hdl:11250/2507194
Keywords: 330